(3MQR GdCeGfj hhLg GdJgGfjs - (3GdQYjfj, GdTGWHj, CHh eMeO, GdbGSe Hf pajoqQg Hf Nda Hf CMeO, J (B590 (3g`s
(3ChdgG (B:s
(3HOCJ HHSe Gddg aj GdfXe ChdG (B- (3JHGQc QMeGfG QMjeG heFdG (B- (3hKfjJ Udi Gddg QHj Ydi GdQVG (B- (3eMeO GdegOj Edj GdfGS eQSdG (B- (3hYJQJg Ke GdUMGHI Ke ef (B- (3JdGge Ydi GdEMSjGf HGdNjQ ohqHdGs
(3BNQgG (B:s
(3hHYO UdGI Gddg Kqe SdGeg Ydi SqjO GdNdb GdQVG eJfqNdG (B- (3eMqeO GdeNJGQ ddeLO cYHI UdGI JHGQj GdQjM eScG hefOdG (B- (3hJHOj Ydi CUMGHg faMGJgG HZjQ JfGg RQfHG hbQfadGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 180s
(3eYLe GdeDdajf (B2 / 647s
(3cTa GdXfhf (B1 / 646s
(3TPQGJ GdPgH (B4 / 301s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs